RUSSIA - MONGOLIA FROM THE 1990S TO 2016: ON THE WAY OF STRATEGIC PARTNERSHIP - Ganhuyag, E. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2017)
In the article the author analyzes the development process of the interstate relations of Mongolia and Russia from the 1990s to 2016: the role of internal and external factors that in-ﬂ uenced the Russian-Mongolian relations. The author shows that from the Declaration of independence in 1911 up to the end of the 1980s, the history of Mongolia was closely associated with the Soviet Union. With the Soviet help, Mongolia turned into a developed, modern state from a backward region of the Chinese Empire. The USSR was Mongolia’s reliable ally, the guarantor of indepen-dence and a generous sponsor. With the beginning of Perestroika, the new Russian leadership abandoned their former allies and friends, and began to build friendly relations with Western countries. Mongolia was left without support and help of its powerful neighbour. In its turn, the Mongolian leadership managed to ﬁ nd new economic partners. Western companies began to invest in the mining industry of Mongolia. The author comes to the conclusion that the positive historical experience of the Russian-Mongolian intergovernmental relations suggests that in the current difﬁ cult conditions of sha-ping the new world order, Russia could provide Mongolia with considerable political and diplomatic support towards the development of the Mongolian state and bilateral relations. In the evolving political and military situation in the Asia-Paciﬁ c region, the author justiﬁ es the need for further development of Mongolia-Russia relations.